Reliability of automated synovial fluid cell counting with Mindray BC‐6800 body fluid mode. (6th March 2017) - Buoro, S.; Seghezzi, M.; Manenti, B.; Mecca, T.; Candiago, E.; Vidali, M.; Ottomano, C.; Castelli, C.C.; Ferrari, R.; Zappalà, G.; Lippi, G.
Abstract: Introduction: The enumeration and differentiation of nuclear elements in synovial fluid is a cornerstone for diagnosis and follow‐up of many orthopedic and rheumatologic diseases. In this study, we evaluated the analytical performance of Mindray BC‐6800 BF mode (BC‐6800‐BF) for synovial fluid analysis. Methods: Overall, 78 synovial fluids were collected and analyzed with both BC‐6800‐BF and light microscopy. The study also entailed the assessment of limit of blank (LoB), limit of detection (LoD), limit of quantification (LoQ), carryover and linearity. Results: The LoB for the parameters total cells and white blood cells was 6 × 10 6 cells/L, and the LoD and LoQ were instead 15 and 16 × 10 6 cells/L, respectively. Linearity was excellent and carryover was negligible. The agreement between BC‐6800‐BF and light microscopy was satisfactory for all samples pretreated with hyaluronidase, displaying a bias between −5.9% and 8.2%. Conclusions: The use of BC‐6800‐BF for synovial fluid analysis enables rapid and accurate assessment, especially for total cell and polymorphonuclear counts. The use of BC‐6800‐BF may therefore allow the replacement of optical analysis, especially in samples pretreated with hyaluronidase, thus allowing its routine use for the screening of synovial specimens.